Dataset for the characterisation of thermal stratification in horizontally configured electric water heaters - P.D. van Schalkwyk; J.A.A. Engelbrecht; M.J. Booysen (Data in Brief, 2024)
A test station was designed and built to measure the thermal stratification (vertical thermal gradients) in a horizontal 150 L electric water heater storage device for different external environmental and user-emulating inputs, ambient temperature, inlet water temperature, water draw flow rate, thermostat temperature and heating coil active time. Stratification measurement consists of 66 temperature sensors that coarsely map three-dimensional temperature gradients within the horizontally configured heating device, under different operational conditions. Other significant temperatures such as inlet, outlet, ambient, thermostat feedback, and wall temperatures were also recorded. An ambient temperature control (climatic) chamber was built to emulate the environmental conditions.A custom-built controller was used to control thermal actuators, the power to the thermostat and the state of the outlet valve. In addition, it also acted as a data acquisition system, responsible for recording all relevant sensor data that was present in the system as well as the test station operating states.The dataset includes heating and thermostat control data and the corresponding thermal stratification profiles under static operating conditions (no water draw) at different ambient temperatures (20 °C, 30 °C, and 40 °C).Additionally, dynamic operating conditions (with water draw) are recorded, maintaining inlet water temperatures at approximately 10 °C and 30 °C. The dataset highlights thermal profiles with and without thermostat control and ambient cooling data without thermostat control.Existing research primarily focuses on vertically oriented water heaters, with limited attention to thermal modelling and data acquisition in horizontal configurations. This work provides valuable insights into the internal thermal dynamics of horizontally configured electric water heater storage devices, widely used worldwide.